Голосовое управление как способ взаимодействия человека с машиной - Гелетто, В. М. (ХНУРЕ, 2020)
A voice-user interface (VUI) makes spoken human interaction with computers possible, using speech recognition to understand spoken commands and answer questions, and typically text to speech to play a reply. A voice command device (VCD) is a device controlled with a voice user interface. Voice user interfaces have been added to automobiles, home automation systems, computer operating systems, home appliances like washing machines and microwave ovens, and television remote controls.
Keywords: голосове управління; оцифровані дані; модульна архітектура